Coordination between Bradyrhizobium and Pseudomonas alleviates salt stress in soybean through altering root system architecture. Issue 1 (1st January 2017) - Egamberdieva, Dilfuza; Wirth, Stephan; Jabborova, Dilfuza; Räsänen, Leena A.; Liao, Hong
ABSTRACT: It is a well accepted strategy to improve plant salt tolerance through inoculation with beneficial microorganisms. However, its underlying mechanisms still remain unclear. In the present study, hydroponic experiments were conducted to evaluate the effects of Bradyrhizobium japonicum USDA 110 with salt-tolerant Pseudomonas putida TSAU1 on growth, protein content, nitrogen, and phosphorus uptake as well as root system architecture of soybean ( Glycine max L.) under salt stress. The results indicated that the combined inoculation with USDA 110 and TSAU1 significantly improved plant growth, nitrogen and phosphorus contents, and contents of soluble leaf proteins under salt stress compared to the inoculation with the symbiont alone or compared to un-inoculated ones. The root architectural traits, like root length, surface area, project area, and root volume; as well as nodulation traits were also significantly increased by co-inoculation with USDA 110 and TSAU1. The plant-growth promoting rhizobacteria (PGPR) P. putida strain TSAU1 could improve the symbiotic interaction between the salt-stressed soybean and B. japonicum USDA 110. In conclusion, inoculation with B. japonicum and salt-tolerant P. putida synergistically improved soybean salt tolerance through altering root system architecture facilitating nitrogen and phosphorus acquisition, and nodule formation.